TEKANAN PENGARUH SOSIAL DALAM MENJELASKAN HUBUNGAN MORAL REASONING TERHADAP KEPUTUSAN AUDITOR - Faisal, Faisal (UI Scholars Hub, 2007)
This research examines whether social influence pressure within the accounting firms affect auditor's willingness to sign-off on financial statements that are materially misstated. This paper also examines the effect o f moral reasoning as variable that may impact individual responses to social influence pressures. A sample o f 92 students from Pendidikan Profesi Akuntansi (PPAk) participated in a between-subjects experiment. The results support the hypothesis that obedience and conformity pressures significantly increased auditor 's willingness to sign-off on account balance that was materially misstated. On the other hand, the result shows that moral reasoning does not have effect to auditors ’ decisions under social influence pressure.